IMPLEMENTATION OF THE RIAU HOMELAND OF MALAY BRAND AS A MEANS OF PROMOTING TOURISM I - Andi Arifin Siregar; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Riau Homeland of Melayu tourism promotion brand is a tourism promotion brand in Riau Province. Riau Homeland of Melayu at the same time becomes the identity and identity of Riau Province. Riau Homeland of Melayu describes the unity of the various elements of tourism and culture in the province of Riau and presents how nature, culture and other extraordinary advantages have increased the tourist attraction for Riau visitors. A qualitative method with a descriptive approach, where the researcher tries to describe the actual conditions and conditions by collecting data and information in the field and explained in the form of a description without testing hypotheses or making predictions in advance used in making this research. In this study, it is explained as a tourist attraction to find out tourism in Malay lands which is a tourist attraction to visit Riau Province. Based on the research results, Brand Riau Homeland of Melayu in Riau Province is in the fairly good category. Keywords: Brand, Promotion, Riau homeland of Melayu.